(untitled) (AYUSHDHARA, 2019)
Objective: The present study intended to focus on the disease evaluation i.e., Gridhrasi – Sciatica and effect of selective Yoga Techniques in the management of Gridhrasi - Sciatica” was undertaken. Clinical source: Patients of Gridhrasi attending Swasthavritta O.P.D and camps conducted by S.J.G Ayurvedic Medical College, P.G Studies and Research center, Koppal. Study Design: Yoga Techniques are used Ardhakati Chakrasana, Ardha Shalabhasana (half locust pose), Shalabhasana (full locust pose), Bhujangasana for 60 days, Treatment duration was 30 days. 15 patients full filling the inclusion criteria of Gridhrasi were randomly selected and advised for Yoga techniques in morning. Parameters are Stambha (stiffness), Ruk (pain), Toda (pricking sensation), Spandana (twitching), and SLR test Results: Shown significant effect after the treatment.